Research on the human virome: where are we and what is next. Issue 1 (December 2016) - Zou, Shimian; Caler, Lis; Colombini-Hatch, Sandra; Glynn, Simone; Srinivas, Pothur
Abstract The National Heart, Lung, and Blood Institute (NHLBI) of the National Institutes of Health convened a Working Group on the Microbiome in Cardiovascular, Pulmonary and Hematologic Health and Diseases from June 25, 2014, to June 26, 2014. The Working Group's central goal was to define what major microbiome research areas warranted additional study in the context of heart, lung, and blood (HLB) diseases. The Working Group identified studies of the human virome a key priority.